2022
DOI: 10.15252/emmm.202115295
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of the pro‐fibrotic reaction mediated by the miR‐143/‐145 cluster enhances the responses to targeted therapy in melanoma

Abstract: Lineage dedifferentiation toward a mesenchymal‐like state displaying myofibroblast and fibrotic features is a common mechanism of adaptive and acquired resistance to targeted therapy in melanoma. Here, we show that the anti‐fibrotic drug nintedanib is active to normalize the fibrous ECM network, enhance the efficacy of MAPK‐targeted therapy, and delay tumor relapse in a preclinical model of melanoma. Acquisition of this resistant phenotype and its reversion by nintedanib pointed to miR‐143/‐145 pro‐fibrotic cl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 67 publications
1
11
0
Order By: Relevance
“…In addition to melanoma cellular proliferation, these findings suggest a role of PSMD14 within the EMT process, as also observed in breast and esophageal cancers [ 100 , 101 ]. Hence, PSMD14 activity or expression may mediate the EMT phenotype that is associated with tumor progression, metastasis, and drug resistance [ 102 , 103 , 104 ]. Recently, capzimine has been developed as a selective inhibitor of PSMD14.…”
Section: Deubiquitinating Enzymes In Melanomamentioning
confidence: 99%
“…In addition to melanoma cellular proliferation, these findings suggest a role of PSMD14 within the EMT process, as also observed in breast and esophageal cancers [ 100 , 101 ]. Hence, PSMD14 activity or expression may mediate the EMT phenotype that is associated with tumor progression, metastasis, and drug resistance [ 102 , 103 , 104 ]. Recently, capzimine has been developed as a selective inhibitor of PSMD14.…”
Section: Deubiquitinating Enzymes In Melanomamentioning
confidence: 99%
“…Another strategy might be to identify novel druggable targets in melanoma cells that promote the ECM remodeling abilities associated with the dedifferentiated, mesenchymal-like and resistant phenotype in melanoma cells. We recently identified a fibrosis-associated miRNA cluster (miR-143/-145) that was shown to play an important role in driving the ECM program in dedifferentiated, invasive and mesenchymal-like melanoma cells (15). Furthermore, we also found that, in an allograft melanoma model, the anti-fibrotic drug Nintedanib was efficient in preventing miR-143/-145 cluster upregulation in melanoma cells and in combination with MAPK targeting therapy, normalized the tumoral ECM niche and delayed relapse (15).…”
Section: Strategies To Normalize the Tmementioning
confidence: 99%
“…The ECM is rich in proteins that form a 3D-meshwork of varying alignment and stiffness. Importantly, in cancers including melanoma, the ECM is drastically remodeled resembling fibrosis, especially during invasion and in response to therapies (12)(13)(14)(15). This review begins with an overview of melanoma, including disease progression, current therapies and phenotypic plasticity, followed by a description of how ECM architecture is modified in the melanoma TME.…”
Section: Introductionmentioning
confidence: 99%
“…Remarkably, several recent studies on melanoma treatment have demonstrated that the efficacy of MAPK‐targeting therapies, [16,17] and immunotherapies [18] are significantly improved by the co‐administration of nintedanib, thus emphasizing the role of this small molecule in TME normalization.…”
Section: Introductionmentioning
confidence: 99%
“…[14] Nintedanib, a small-molecule tyrosine kinase inhibitor, clinically approved as an antifibrotic drug, inhibits the accumulation and activation of fibroblasts so too their transition into myofibroblasts, as well as the deposition of the ECM. [15] Remarkably, several recent studies on melanoma treatment have demonstrated that the efficacy of MAPK-targeting therapies, [16,17] and immunotherapies [18] are significantly improved by the co-administration of nintedanib, thus emphasizing the role of this small molecule in TME normalization.…”
Section: Introductionmentioning
confidence: 99%